FRI0455 Increasing incidence of adult idiopathic inflammatory myopathies: a ten-year uk epidemiological study. (12th June 2018) - Parker, M.J.S.; Oldroyd, A.; Roberts, M.E.; Cooper, R.G.; Chinoy, H.; ,
Abstract : Background: Studying the epidemiology of rare conditions such as the idiopathic inflammatory myopathies (IIM) can assist in the identification of risk factors, disease associations and temporal trends. Interrogation of differing geographically and genetically diverse populations can help to construct a more complete picture of underlying disease patterns. A number of UK centres have contributed to national and international IIM research collaborations, but to date there has been no published report detailing the incidence or prevalence of adult IIM in the UK, or to establish the relative proportion of the varying clinical subtypes. Moreover, previous international studies have focussed on specific IIM subtypes, such as inclusion body myositis (IBM) or immune-mediated necrotising myopathy (IMNM), are historic, were undertaken before recent developments in our understanding of the range of IIM subtypes, and utilised widely varying methodologies and case acquisition strategies. The recently published combined European League Against Rheumatism and American College of Rheumatology (EULAR/ACR) classification criteria for adult and juvenile IIM represent potential progress in identifying IIM, as well as various disease subtypes 1 . We present here the first epidemiological study to utilise these new criteria as part of disease verification. Objectives: Identify and characterise all incident adult cases of IIM between Jan 1 st 2007 and Dec 31 st 2016 in the City of Salford, UK. Methods: Adults first diagnosed with IIM within the study period were identified by: i) a Salford Royal NHS Foundation Trust (SRFT)inpatient episode IIM-specific ICD-10 coding search; ii) all new patient appointments to SRFT neuromuscular outpatient clinics; iii) all Salford residents enrolled within the UKMYONET study. All patients with 'definite' IIM by the 2017 EULAR/ACR classification criteria were included, as were 'probable' cases if expert opinion agreed. Cases were excluded if <18 years at disease onset, if they did not meet 'probable' criteria, or when 'probable' but expert opinion concluded a non-IIM diagnosis. Results: The case ascertainment procedures identified 1156 cases which, after review and application of exclusion criteria, resulted in 32 incident cases during the study period. 23/32 were female with a mean age of 58.1 years. The mean incidence of adult IIM was 17.6/1, 000, 000 person years (py), higher for females than for males (25.2 versus 10.0/1, 000, 000py respectively). A significant incidence increase over time was apparent (13.6 versus 21.4/1, 000, 000py; p=0.032). Using EULAR/ACR classification criteria, the largest IIM subtype (21/32) was polymyositis, followed by dermatomyositis (8/32), inclusion body myositis (2/32) and amyopathic dermatomyositis (1/32). Expert opinion subtype differed from EULAR/ACR Classification criteria in 19/32 cases. Conclusions: The incidence of adult IIM in Salford is 17.6/1, 000, 000py, higher in females and is increasing over time. Disagreement exists between EULAR/ACR-derived and expert opinion-derived IIM subtype assignments. References: [1] Lundberg IE, Tjärnlund A, Bottai M, et al. EULAR/ACR Classification Criteria for Adult and Juvenile Idiopathic Inflammatory Myopathies and their Major Subgroups. Ann Rheum Dis. 2017;76:1955–64. Disclosure of Interest: None declared